Women librarians’ training and Women’s Libraries in Spain - Muñoz-Muñoz, Ana M.; Argente Jiménez, Montse (Revista General de Información y Documentación, 2015)
Since the end of the 19th century, women have accessed library training and in the start of the 20th century, first women’s libraries appear are created in Spain. This study addresses access of women to library training, feminizing the profession and influencing the creation of women’s libraries. In order to do so, a review of recent history is performed. On the one hand, analyzing women’s training in Higher Education and in programs developed by different Spanish institutions. On the other hand, analyzing the creation and the increasing importance women’s libraries have had. Although these two topics had independent developments, it becomes clear that women’s inclusion in library studies training fostered the creation of women’s libraries.